Optimalisasi Pemantauan Deteksi Dini Tumbuh Kembang Anak melalui Aplikasi “PRIMAKU” - Inung Diah Kurniawati; Oyin Anjam Ainurrosidah (CV. ITTC INDONESIA, 2024)
Monitoring children's growth and development is crucial. Children's growth and development needs to be done from an early age, so that children's development can grow optimally. Monitoring of children's growth and development is carried out by trained health workers and also by the child's parents. The process of monitoring children's growth and development can be done through posyandu activities and can also be done through applications. One of them is the